2020
DOI: 10.1007/jhep08(2020)120
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous decay rate of quasinormal modes in Schwarzschild-dS and Schwarzschild-AdS black holes

Abstract: Recently an anomalous decay rate of the quasinormal modes of a massive scalar field in Schwarzschild black holes backgrounds was reported in which the longest-lived modes are the ones with higher angular number, for a scalar field mass smaller than a critical value, while that beyond this value the behaviour is inverted. In this work, we extend the study to other asymptotic geometries, such as, Schwarzschild-de Sitter and Schwarzschild-AdS black holes. Mainly, we found that such behaviour and the critical mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
(69 reference statements)
7
14
0
Order By: Relevance
“…The f (R) gravity is a modified gravitational theory where the action is given in a generic form of scalar curvature R and the f (R) gravity may describe the early and late cosmological evolution. The f (R) theory can describe dark energy and dark matter consistently without imposing any new material that has not yet been revealed by experiments [2][3][4][5][6][7]. Amending the Lagrangian of general relativity (GR) does not only influence the dynamical system of the universe but it can also change the dynamical system at the galactic or solar system scales.…”
Section: Introductionmentioning
confidence: 99%
“…The f (R) gravity is a modified gravitational theory where the action is given in a generic form of scalar curvature R and the f (R) gravity may describe the early and late cosmological evolution. The f (R) theory can describe dark energy and dark matter consistently without imposing any new material that has not yet been revealed by experiments [2][3][4][5][6][7]. Amending the Lagrangian of general relativity (GR) does not only influence the dynamical system of the universe but it can also change the dynamical system at the galactic or solar system scales.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore we note that for β negative (positive) the potential diverges positive (negative) at infinity, and in principle the existence of a critical mass could not be present in this case, due to the arguments given in [68]. Now, in order to solve numerically the differential equation ( 9) by using the pseudospectral Chebyshev method [82], it is convenient to perform the change of variable y = (r − r H )/(r − r H ).…”
Section: Scalar Perturbationsmentioning
confidence: 91%
“…The study of the anomalous behavior of QNMs was extended to other asymptotic geometries, such as, Schwarzs -child-de Sitter and Schwarzschild-AdS black holes in [68]. It was found that the same behavior is present in the Schwarzschild-de Sitter background, i.e., the absolute values of the imaginary part of the QNFs decay when the angular harmonic numbers increase if the mass of the scalar field is smaller than the critical mass, and they grow when the angular harmonic numbers increase, if the mass of the scalar field is larger than the critical mass.…”
Section: (): V-volmentioning
confidence: 99%
See 1 more Smart Citation
“…For scalar perturbations (S = 0), one must solve the massless Klein-Gordon equation, ψ(r) = 0; whilst for electromagnetic (S = 1) perturbations, one must analyse the the electromagnetic four-potential subject to Maxwell's equations. Further details can be found in references [7,23,114,120]. For spin 0 and spin 1 perturbations, this yields the result [20,128]: Hence,…”
Section: Regge-wheeler Potentialmentioning
confidence: 86%